Polyamine auxotrophs of Saccharomyces cerevisiae. - Whitney, P A (1978)
Strains of yeast have been constructed that are unable to synthesize ornithine and are thereby deficient in polyamine biosynthesis. These strains were used to develop a protocol for isolation of mutants blocked directly in polyamine synthesis. There were seven mutants isolated that lack ornithine decarboxylase activity; these strains exhibited greatly decreased pool levels of putrescine, spermidine, and spermine when grown in the absence of polyamines. Three of the mutants lack S-adenosylmethionine decarboxylase activity; polyamine limitation of a representative mutant resulted in an accumulation of putrescine and a decrease in spermidine and spermine. When the mutants were cultured in the absence of polyamines, a continuously declining growth rate was observed.